Killer instinct lizards - Gibson, Garry; Gibson, Michael R. ([S.l.] : Starcast, 2001)
Rob Bredl brings new understanding to the Komodo Dragons, the largest monitor on earth, and compares them with their Australian cousins the goannas. He also introduces us to the perentie, known by the Australian Aboriginal people as a'Land Crocodile.' Rob gleefully gets his hands on some serious lizards surviving in extreme environments on pure killer instinct
Title from title screen
Executive producer, Paul Sharrant ; editors, Ross McIntosh, Jason Larry, Marion Gibson
Host: Rob Bredl
Narrated by Michael R. Gibson
DVD Format
Keywords: Lizards